Newborn Genetic Screening-Still a Role for Sanger Sequencing in the Era of NGS - Silje Hogner; Emma Lundman; Janne Strand; Mari Eknes Ytre-Arne; Trine Tangeraas; Asbjørg Stray-Pedersen (MDPI AG, 2023)
In the Norwegian newborn screening (NBS) program, genetic testing has been implemented as a second or third tier method for the majority of NBS disorders, significantly increasing positive predictive value (PPV). DNA is extracted from dried blood spot (DBS) filter cards. For monogenic disorders caused by variants in one single gene or a few genes only, Sanger sequencing has been shown to be the most time- and cost-efficient method to use. Here, we present the Sanger sequencing method, including primer sequences and the genetic test algorithms, currently used in the Norwegian newborn screening program.